KINERJA PORTOFOLIO REKSADANA SYARIAH DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Iswadi, Iswadi; Agustina, Agustina (Jurnal Akuntansi dan Keuangan, 2019)
This study aims to determine the performance of the Sharia Mutual Fund portfolio on the Indonesia Stock Exchange. The data used in this study are primary data is the performance of Islamic mutual fund portfolio in the Indonesian stock exchange. The data used are data from January 2013 to December 2017 consisting of 18 names of stock mutual funds that have reached the target of the last five years. While the type of research used is qualitative descriptive research, namely researchers analyzing the performance of the Sharia Mutual Fund portfolio on the Indonesia Stock Exchange. The results showed that the performance of the Sharia Mutual Fund portfolio in the Indonesia Stock Exchange during the last five years 2013-2017 experienced fluctuations and was able to record a fairly good performance and tended to move positively due to higher JCI value as a form of investor confidence in Indonesia's increasingly conducive economic conditions.